2013
DOI: 10.1002/jbm.a.34825
|View full text |Cite
|
Sign up to set email alerts
|

Jagged1 immobilization to an osteoconductive polymer activates the Notch signaling pathway and induces osteogenesis

Abstract: Treatment of nonunion fractures is a significant problem. Common therapeutics, including autologous bone grafts and bone morphogenetic proteins, show well-established limitations. Therefore, a need persists for the identification of novel clinical therapies to promote healing. The Notch signaling pathway regulates bone development. Clinically, loss-of-function mutations to the Notch ligand Jagged1 decrease bone mass and increase fracture risk. Jagged1 is also the most highly upregulated ligand during fracture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 34 publications
(74 reference statements)
0
58
0
Order By: Relevance
“…Conversely, inhibition of NOTCH signaling in MC3T3 cells was shown to result in decreased regulators of bone development: RUNX2, Alkaline Phosphatase, Collagen1 , and Osteocalcin [7]. Several recent studies demonstrated that JAG1 acts to induce mesenchymal stem cells to differentiate into osteoblasts and undergo mineralization [5, 30]. In these studies, JAG1 induced expression of bone sialoprotein and Alkaline Phosphatase , demonstrating the role of JAGGED1 during the induction of mesenchymal cells into osteoblasts [30].…”
Section: 1 Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, inhibition of NOTCH signaling in MC3T3 cells was shown to result in decreased regulators of bone development: RUNX2, Alkaline Phosphatase, Collagen1 , and Osteocalcin [7]. Several recent studies demonstrated that JAG1 acts to induce mesenchymal stem cells to differentiate into osteoblasts and undergo mineralization [5, 30]. In these studies, JAG1 induced expression of bone sialoprotein and Alkaline Phosphatase , demonstrating the role of JAGGED1 during the induction of mesenchymal cells into osteoblasts [30].…”
Section: 1 Discussionmentioning
confidence: 99%
“…Several recent studies demonstrated that JAG1 acts to induce mesenchymal stem cells to differentiate into osteoblasts and undergo mineralization [5, 30]. In these studies, JAG1 induced expression of bone sialoprotein and Alkaline Phosphatase , demonstrating the role of JAGGED1 during the induction of mesenchymal cells into osteoblasts [30]. In addition, mutations in Jag1 cause Alagille syndrome in humans which is associated with craniofacial defects, butterfly vertebrae, digit abnormalities, osteoporosis, and pediatric bone fractures, suggesting that JAG1 plays an important role in human bone development and maintenance [31].…”
Section: 1 Discussionmentioning
confidence: 99%
“…While endothelial Notch activity was reported as an essential source for the coordinated osteogenesis and angiogenesis during the bone development [44], it is not clear if it's necessary to include endothelial progenitors in engineered bone tissues to achieve Notch-induced angiogenesis. It was reported that the expression of Notch ligand Jaggedl was able to induce osteogenesis [78], whereas the genetic deletion of Jaggedl resulted in defects in osteoblast development and differentiation during maxillary ossification [79]. We previously found that the downstream target gene of Notch signaling Heyl was upregulated by BMP9 [28], suggesting BMP9 may act upstream of Notch signaling.…”
Section: Discussionmentioning
confidence: 99%
“…3,[405][406][407][408][409][410][411][412][413]2017 Original Notch signaling partly regulates the osteogenic differentiation of retinoic acid-treated murine induced pluripotent stem cells Thanaphum Osathanon 1) , Jeeranan Manokawinchoke 1) , Hiroshi Egusa 2) , and Prasit Pavasant 1) must be clarified in order to ensure that their complete differentiation results in bone regeneration, without the development of teratomas. Notch signaling regulates several differentiation processes (5)(6)(7)(8)(9), including bone healing. Increased expression of various Notch signaling components has been observed in healing tibial and calvarial fractures (10).…”
Section: Introductionmentioning
confidence: 99%